Enhanching Vocabulary Mastery By The Usage Of Elicitation Technique At The Third Semester Of English Language Education STKIP PGRI Nganjuk In The 2020/2021 Academic Year - Rina Puji Utami; Henny Roessalaningtias (Dharma Pendidikan, 2021)
Abstract The purpose of research is to find out comptence of students’ vocabulary mastery before and after taught by using elicitation technique and to find out the effectiveness of using elicitation technique before and after in students’ vocabulary mastery at the third semester of English Language Education STKIP PGRI Nganjuk . The methodology of research is experimental research, one group pre-test post-test design. The research was conducted at STKIP PGRI Nganjuk, at the academic year of 2020/2021 by using the samples at the third semester of English Language Education class by number of class is 26 students. In completing the research, the technique of data collection used test. Analysis of the data is used t-test. Based on the table above it could be seen that tcount had greater than ttable at level of significant. tcount is 11, 47 an ttable on the significant level of 5% is 2.04523. Based on the results of analysis that tcount > ttable there is effectiveness to develop the students’ vocabulary mastery before and after being taught using elicitation technique at the third semester of English Language Education STKIP PGRI Nganjuk at the 2020/2021 academic year. The hypothesis is Ha is accepted and Ho is rejected. That is : “ There is effectiveness between teaching vocabulary using Elicitation Technique and teaching vocabulary without using Elicitation Technique to enhance students’ vocabulary mastery at the third semester of English Language Education STKIP PGRI Nganjuk at the 2020/2021 academic year.